Strength and weakness of the Old English adjective - Malak, Janusz (Adam Mickiewicz University, 2021)
As regards Old English, the inflectional strength and weakness are characterised by a kind of inconsistency. In the case of Old English adjectives these two inflectional properties appear to be different from those associated with nouns and verbs. In the case of the latter the two properties seem to be lexically determined while in the case of adjectives they appear to be determined by syntactic conditions. The traditional accounts of the Old English grammar attribute two paradigms to one adjectival lexical item. The analysis presented in this article postulates that one can actually speak about one adjectival inflection and what is traditionally presented as strong and weak adjectival inflections is actually the result of two different syntactic derivations.
Keywords: Old English; strong inflection; weak inflection; adjective; adjective; Lexical Item